OPERATOR PERFORMANCE ASSESMENT AT PT. DARIA DHARMA PRATAMA BY USING AHP AND RATING SCALE METHOD - Damres Uker; Meizul Zuki; Ruth Berliana Simanjuntak (BPFP Faperta UNIB, 2018)
Performance assessment is the process of evaluating and assessing employee performance. This activity can improve personnel decisions and provide feedback to employees about the implementation of their works.. The purpose of this research is to apply AHP method and rating scale in assessing the performance of CPO factory operators in PT. Daria Dharma Pratama Lubuk Bento with predetermined criteria. The research method used is the questionnaire method (questionnaire), where the authors submit the questionnaire directly to the respondents and take it back. Data analysis used AHP method to get global weight from each criteria and sub criteria and combined with rating scale which aims to assess operator's performances with scale of assessment then look for recapitulation of operator performances result from both methods. Based on the results of the research, it is found that the criteria that are the first priority in assessing operator performances are the attitude criteria and the sub criteria which becomes the first priorities are minor care, self-safety, clothing and personal protective equipment.Keywords: Performance assessment, AHP, rating scale